Pro‐survival signal inhibition by CDK inhibitor dinaciclib in Chronic Lymphocytic Leukaemia. (29th July 2016) - Chen, Yixiang; Germano, Sandra; Clements, Chris; Samuel, Jesvin; Shelmani, Ghalia; Jayne, Sandrine; Dyer, Martin J. S.; Macip, Salvador
Summary: Dinaciclib is a cyclin‐dependent kinase inhibitor with clinical potential in different cancers, including chronic lymphocytic leukaemia (CLL). In order to better understand its cytotoxic action, we characterized its effects on signalling pathways important for the survival of CLL cells. We found that dinaciclib induced apoptosis through the activation of caspases 8 and 9, which was independent of the presence of cytokines to mimic the environment of proliferation centres or IGVH mutation status. Moreover, treatment with dinaciclib led to the inhibition of oncogenic pathways normally activated in stimulated CLL cells, such as STAT3, NF‐κB, p38, PI3K/AKT and RAF/MEK/ERK. Dinaciclib was also able to block the expression of anti‐apoptotic proteins of the BCL2 family such as MCL1 and BCL‐xL (also termed BCL2L1). Finally, we showed that low concentrations of dinaciclib enhanced cell sensitivity to ibrutinib and the BCL2 inhibitor ABT‐199, two drugs with known effects on CLL. Taken together, our data show that dinaciclib targets multiple pro‐survival signalling pathways in CLL, which provides a mechanistic explanation for its potent induction of apoptosis. They also support a therapeutic application of cyclin‐dependent kinase inhibitors in CLL in combination with other relevant targeted therapies.